Investigation and experimental evaluation of a mono-pixel X-ray system in healthcare - Steinert, Jule; Salamon, Michael; Wittenberg, Thomas (Current Directions in Biomedical Engineering, 2024)
The acquisition of two-dimensional X-ray images (of non-human objects) is quite expensive, primarily due to the costly flat-panel or line detectors. Reducing these costs could open up new possibilities in healthcare applications, such as inspecting limb prostheses for cracks and defects or safety-related material testing of helmets and child seats. In this contribution, two different setups of low-cost mono-pixel X-ray scanners are described: a small scanner with a working volume of 20 x 20 x 20 cm3 and a large system with a volume of 150 x 230 x 110 cm3. Using these novel mono-pixel X-ray scanning systems, various objects - ranging from an X-ray phantom and a human skull phantom to a high-end limb prosthesis with integrated electronics - were scanned and investigated. Compared to conventional X-ray systems, the mono-pixel systems can depict these objects without the distortion problems of cone beam detectors. Although the scanning procedure is time-consuming, the results are quite promising. Mono-pixel X-ray-scanning is a novel modality capable of scanning largescale objects with low-dose radiation. While it is currently not suitable for human applications due to the long scanning times, it can still be used for the non-destructive testing of large-scale medical devices, such as e.g. arm and leg prosthesis.
CRIS-Team Scopus Importer:2024-10-04
Keywords: evaluation; NDT; one-pixel; X-ray technologies